2018
DOI: 10.1371/journal.pone.0197585
|View full text |Cite
|
Sign up to set email alerts
|

Eye position affects flight altitude in visual approach to landing independent of level of expertise of pilot

Abstract: The present study addresses the effect of the eye position in the cockpit on the flight altitude during the final approach to landing. Three groups of participants with different levels of expertise (novices, trainees, and certified pilots) were given a laptop with a flight simulator and they were asked to maintain a 3.71° glide slope while landing. Each participant performed 40 approaches to the runway. During 8 of the approaches, the point of view that the flight simulator used to compute the visual scene wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…However, perceptual-motor processes may not reach the pilots’ awareness. Virtual reality setups thus allow more finely grained experimental methods that can be used in complement to track perceptual information picked up when landing [ 13 ]. Indeed, the more rooted the aid is in the perceptual-motor principles used by pilots, the more efficient the aid will be [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, perceptual-motor processes may not reach the pilots’ awareness. Virtual reality setups thus allow more finely grained experimental methods that can be used in complement to track perceptual information picked up when landing [ 13 ]. Indeed, the more rooted the aid is in the perceptual-motor principles used by pilots, the more efficient the aid will be [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other more complex scenarios can also allow detecting the perceptive expertise of players more precisely. In the same way that contextual information was neutralized using VR in this paper, other manipulations are possible including spatial 34 and temporal occlusion, 50 , 51 as well as decorrelation 52 of the several sources of information available in the visual scene. These manipulations could be utilized to infer the contribution of visual information to the regulation and for regulating the motion.…”
Section: Discussionmentioning
confidence: 99%
“…In current flights, navigation instruments and warning systems on the flight path (Ground Proximity Warning System (GPWS) and Terrain Avoidance and Warning System (TAWS)) and, at lower altitudes, ILS, along with the pilot's natural vision, provide accurate information about the position, attitude, and flight environment. Recent research has shown that a pilot's inadequate visual perception can endanger the landing phase [2].…”
Section: Visual Navigation Instruments In Landingmentioning
confidence: 99%
“…Today, aeronautical engineers are looking for new methods to overcome the problems associated with limited pilot visibility, by introducing many new measurements and avionics (e.g., aircraft status indicators, radio navigation, inertial landing system, and ground proximity warning systems) [1]. However, landing is still one of the most accident-prone ight phases, with a relatively high percentage of fatal and nonfatal air accidents [1,2]. It has been reported that almost half of plane crashes occur in the approach and nal landing stages [3].…”
Section: Introductionmentioning
confidence: 99%